2002
DOI: 10.1145/543552.512556
|View full text |Cite
|
Sign up to set email alerts
|

Static load classification for improving the value predictability of data-cache misses

Abstract: While caches are effective at avoiding most main-memory accesses, the few remaining memory references are still expensive. Even one cache miss per one hundred accesses can double a program's execution time. To better tolerate the data-cache miss latency, architects have proposed various speculation mechanisms, including load-value prediction. A load-value predictor guesses the result of a load so that the dependent instructions can immediately proceed without having to wait for the memory access to complete.To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Burtscher et al [5] classified load instructions based on the region of memory (stack, heap, or global), the kind of reference (array, field, or scalar) and the type of data (pointer or value). They showed that load instructions for certain classes caused more cache misses than others in C and Java programs.…”
Section: Related Workmentioning
confidence: 99%
“…Burtscher et al [5] classified load instructions based on the region of memory (stack, heap, or global), the kind of reference (array, field, or scalar) and the type of data (pointer or value). They showed that load instructions for certain classes caused more cache misses than others in C and Java programs.…”
Section: Related Workmentioning
confidence: 99%
“…Burtscher, Diwan, and Hauswirth [3] (which we shall call the 'BDH-method' in the rest of the paper) proposed a static classification system for improving value prediction. In the BDH-method, load instructions are classified according to the following criteria:…”
Section: Related Workmentioning
confidence: 99%
“…The heuristic that was suggested [3] is that loads belonging to the union of the classes GAN, HSN, HFN, HAN, HFP and HAP account for most of the misses in a program. It should be noted that their study was performed on traces.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations